Study on Crack-Healing Bacteria Isolated from a Commercial Area in Raipur - Archana Shome; Bhagyashree Deshpande; Prashant Mundeja (International Journal of Medical Toxicology and Legal Medicine, 2024)
This study investigates the isolation, identification, and characterization of bacteria capable of crack healing and other functional applications. A total of 168 bacterial colonies were isolated from alkaline soil samples in Raipur, Chhattisgarh, with 12 being Gram-positive and the remainder Gram-negative. Bacillus species, including Bacillus cohnii, Bacillus subtilis, Bacillus cereus, Bacillus licheniformis, and Bacillus halodurans, were identified through morphological, biochemical, and enzymatic analyses. Among these, Bacillus licheniformis and Bacillus halodurans exhibited superior biofilm formation, exopolysaccharide production, urease activity, endospore formation, and calcium carbonate production, making them highly effective for applications such as concrete modification. Temperature-dependent growth studies revealed that Bacillus halodurans thrived optimally at elevated temperatures, while Bacillus licheniformis and other species showed varying temperature preferences. These findings highlight the potential of selected Bacillus species in biotechnological and industrial applications, particularly in bio-remediation and construction.